Incidence of trigger digits following carpal tunnel release: A nationwide, population-based retrospective cohort study. Issue 27 (July 2017) - Lin, Fu-Yu; Manrique, Oscar J.; Lin, Cheng-Li; Cheng, Hsu-Tang
Abstract : Abstract: The onset of trigger digits after carpal tunnel release (CTR) have been reported inconsistently across different studies. The aim of this study is to assess the incidence of trigger digits after CTR using nationwide population cohort data. We conducted a retrospective cohort study using the Longitudinal Health Insurance Database 2000 (LHID2000) from the National Health Insurance Database (NHIRD) in Taiwan. The LHID2000 contained 1 million beneficiaries randomly selected from the year 2000 Registry for Beneficiaries in NHIRD. We identified 2605 carpal tunnel syndrome (CTS) patients received CTR from 2000 to 2010 (CTR cohort, n = 2605). For each CTR patient, 4 CTS patients without CTR were randomly selected in the control cohort from the general population frequency matched by age, sex, and diagnosed year (non-CTR cohort, n = 10, 420). Both cohorts were followed up until the end of 2011 to investigate the occurrence of trigger digits. Adjusted hazard ratios (aHRs) with 95% confidence interval (CI) of trigger digits were estimated using the Cox proportional hazards model after controlling for age, sex, and comorbidities. The CTR cohort had a mean follow-up period of 5.58 ± 3.18 years and the non-CTR cohort had a mean follow-up period of 5.90 ± 3.10 years. The overall risk of trigger digits was 3.63-fold greater in the CTR cohort than in the non-CTR cohort (incidence rate: 12.6 vs 3.38/1000 person-years, aHR: 3.63, 95% CI, 2.97–4.44). The incidence of postoperative trigger digits was highest in the 1st 6 months (incidence rate: 27.9/1000 person-years, aHR: 9.65, 95% CI, 5.27–17.7) and then significantly decreased over time. CTR was significantly associated with the subsequent development of trigger digits, especially in the postoperative 6 months.